Fuzzy logic based edge detection method for image processing - Moffaq Alawad, Abdulrahman; Abdul Rahman, Farah Diyana; Khalifa, Othman Omran; Abdul Malek, Norun (2018)
Edge detection is the first step in image recognition systems in a digital image processing. An effective way to resolve many information from an image such depth, curves and its surface is by analyzing its edges, because that can elucidate these characteristic when color, texture, shade or light changes slightly. This can lead to misconception image or vision as it based on faulty method. This work presents new fuzzy logic method with an implementation. The objective of this method is to improve the edge detection task. The results are comparable to similar techniques in particular for medical images because it does not take the uncertain part into its account.